Does Corporate Governance Have An Effect On Financial Distress?: Altman Z-Score Approach - Puspitasari, Fransiska Dwi Ratna; Syam, Dhaniel; Irawan, Dwi (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to test and obtain empirical evidence that projected Corporate Governance with managerial ownership, independent commissioners, board of directors, and audit committees affects financial distress. Methodology/approach: The object of this study is all mining sector companies listed on the Indonesia Stock Exchange in 2019-2021. The sample determination technique in this study used the Purposive Sampling method with a total sample of 35 companies. The data analysis technique in this study used the panel data regression testing method with the STATA statistical tool version 15. Findings: The results of the study partially showed that independent commissioners negatively affect financial distress in mining companies. Then for the variables of managerial ownership, board of directors and audit committees have no effect on financial distress. The results of the study simultaneously showed that together the variables of managerial ownership, independent commissioners, board of directors and audit committees had a significant effect on financial distress. Practical implications: These research findings have an impact on stakeholders and policy makers considering business continuity. Originality/value: This research has the latest in the form of modifications to models and objects that are relevant to the Financial Distress.